2004
DOI: 10.1074/jbc.m408846200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gαq/11-selective Inhibitor

Abstract: YM-254890, which was isolated from the culture broth of Chromobacterium sp., inhibits ADP-induced platelet aggregation and has antithrombotic and thrombolytic effects. YM-254890 blocks G␣ q/11 -coupled ADP receptor P2Y1-mediated Ca 2؉ mobilization. Here we report that YM-254890 is a selective G␣ q/11 inhibitor. YM-254890 blocked Ca 2؉ mobilization mediated by several G␣ q/11 -coupled receptors but not by G␣ i -or G␣ 15 -coupled receptor, indicating that phospholipase C␤ activation and subsequent signaling mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
342
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 371 publications
(375 citation statements)
references
References 32 publications
19
342
1
1
Order By: Relevance
“…S2, we used ectopically expressed Gα proteins in lysates from mammalian cells, because both Gα 14 and Gα 16 proteins were difficult to purify. The results of a previous study (5) and those of our studies indicate that YM-254890 selectively inhibits Gα q , Gα 11 , and Gα 14 among mammalian Gα members.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…S2, we used ectopically expressed Gα proteins in lysates from mammalian cells, because both Gα 14 and Gα 16 proteins were difficult to purify. The results of a previous study (5) and those of our studies indicate that YM-254890 selectively inhibits Gα q , Gα 11 , and Gα 14 among mammalian Gα members.…”
Section: Resultssupporting
confidence: 56%
“…Previously, it was reported that YM-254890 blocks agonist-induced GTPγS binding to G q∕11 in crude cell membranes (5). This finding suggests the possibility that YM-254890 directly binds to Gα q and inhibits the GDP/GTP exchange.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Where indicated, LTB 4 (final concentration of 100 nM) (Cayman Chemicals, Ann Arbor, MI) was added along with opsonized zymosan particles. For the inhibition assay, BMM were pretreated with the following reagents and times prior to incubation with zymosan particles: CP105696 (1 M, 30 min), PP2 (5 M, 30 min) (Calbiochem), Piceatannol (20 M, 30 min) (Calbiochem), LY294002 (50 M, 16 h) (Calbiochem), Rac1 inhibitor (NSC23766; 200 M, 16 h) (Calbiochem), pertussis toxin (PTX; 100 ng/ml, 16 h) (List Biological Laboratories, Campbell, CA), and YM-254890 (10 M, 30 min), a kind gift from Dr. J. Takasaki, Astellas Pharmaceutical (22).…”
Section: Methodsmentioning
confidence: 99%
“…For example, BIM-46174 and BIM-46187 apparently interact with most G␣ subunits (11,12), and some selectivity for G␣ q has been reported for BIM-46187 (13). In contrast, YM-254890 (14), and related natural products such as FR900359 (15,16), specifically inhibit G␣ subunits of the G q family (17,18), and a crystal structure of a G protein heterotrimer bound to YM-254890 illustrates that this molecule prevents GDP release and heterotrimer dissociation (19). Unfortunately, synthesis of cyclic depsipeptides is difficult, and YM-254890 remains unavailable from commercial sources.…”
mentioning
confidence: 99%